Fifty shades freed - James, E. L. (New York : Vintage, 2011)
When unworldly student Ana Steele first encountered the driven, damaged young entrepreneur Christian Grey, it sparked a sensual affair that changed both their lives irrevocably. Shocked, intrigued, and ultimately repelled by Christian's singular sexual tastes, Ana demanded a deeper commitment; determined to keep her, Christian agreed. Now, together, they have more--love, passion, intimacy, wealth, and a world of infinite possibilities. But Ana always knew that loving her Fifty Shades would not be easy and being together poses challenges neither of them ever anticipated.
Keywords: Businesspeople -- Fiction; Man-woman relationships -- Fiction; Erotic fiction